2018
DOI: 10.1111/imb.12536
|View full text |Cite
|
Sign up to set email alerts
|

Phenoloxidases are required for the pea aphid's defence against bacterial and fungal infection

Abstract: The pea aphid, Acyrthosiphon pisum, has an incomplete immune system compared to those of other insect species; some conserved components and pathways in other species are missing in its genome. As a core component of the insect immune system, prophenoloxidase (PPO) genes are retained in the pea aphid. Early studies have also shown the presence of phenoloxidase activity in specific tissues or cells in the pea aphid and suggested its involvement in response to immune challenges. In this study, we knocked down th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Little is known about role of microRNAs in the immune system of aphids to date. Previous studies demonstrated the critical roles of phagocytosis, PPO, and ROS in the pea aphid immune system [14][15][16][17][18][19] and suggested the involvement of JNK signaling in the aphid defense against bacteria [20]. However, the precise role of the JNK pathway and interplay between the JNK pathway and other immune responses in pea aphid remain unclear.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about role of microRNAs in the immune system of aphids to date. Previous studies demonstrated the critical roles of phagocytosis, PPO, and ROS in the pea aphid immune system [14][15][16][17][18][19] and suggested the involvement of JNK signaling in the aphid defense against bacteria [20]. However, the precise role of the JNK pathway and interplay between the JNK pathway and other immune responses in pea aphid remain unclear.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…However, pea aphid exerts a hemocyte-mediated response, including phagocytosis and encapsulation, against bacteria and foreign intrusion [14,15]. Recent studies from our and other groups showed that phenoloxidase (PO) is required and/or involved in the immune defense in pea aphid [16,17]. Additionally, ROS play role in the interaction between pea aphid and bacteria [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing just on the highly-resistant lines, we found that several putative insect immunity genes are upregulated by pea aphids in response to wasp parasitism (S1 Table). These include the gene hemocytin (ACYPI003478), which is released by immune cells and plays a role in cell aggregation [39], a clip-domain serine protease (ACYPI008297) thought to activate phenoloxidase [40][41][42], and several other proteases and inhibitors (e.g. ACYPI003807, ACYPI004531).…”
Section: Resultsmentioning
confidence: 99%
“…In insects, PO-mediated melanin formation is involved in a variety of biological functions such as innate immunity, hemolymph clotting, and wound sealing (1–3, 15, 17). Fig.…”
Section: Resultsmentioning
confidence: 99%